PENGEMBANGAN MODEL PEMBELAJARAN MATEMATIKA BERBASIS BUDAYA A’BULO SIBATANG - Baharullah Baharullah; Sri Satriani (Delta: Jurnal Ilmiah Pendidikan Matematika, 2021)
The application of a new paradigm in the form of a learning model that is adopted from outside and adapted in schools requires students and teachers to change their teaching and learning behavior. Constructive interaction between students and their peers, students and teachers, student-teacher problems are very difficult to condition. This is due to conventional teaching which conditions students to passively receive knowledge. This is evident from student activities, students are reluctant to ask the teacher and their friends even though they are given encouragement and motivation. Smart students prefer to work alone and if they have difficulty directly asking the teacher without passing the results of their group discussions. Maximum results are expected to be achieved, if the application of the new paradigm of learning mathematics is more adapted to the natural way students learn mathematics, and is also more in accordance with the essence of developing mathematical thinking skills. Learning is sought to be more meaningful in local culture and in the learning process incorporating cultural systems and cultural values found in the community in the area where students are, therefore, the purpose of this study is to formulate and compile a mathematics learning model based on A'Bulo Sibatang culture in the classroom. V SD in Bulukumba Regency. This type of research is the development of A'Bulo Sibatang-based mathematics learning model through the development of learning models, tools and instruments in an effort to improve the character of students in mathematics learning by implementing local culture in learning. Based on the results of the research, it was found that the a'bulo sibatang-based learning model was valid and met the effective criteria and the level of practicality of the model was in the high category.